Management trainees in Singapore hotel industry. - Chan, Eng Chien. (2013)
Singapore increasingly faces a labor shortage in its hotel industry. Being a labor intensive and service oriented industry, this is a pressing problem as a shortage of skilled manpower and managerial capability will constitute a major hindrance to the overall development of the hotel industry.